Driving Digital Transformation: The Impact of SME Digitalization on Technology Acceptance and Usage in Small and Medium Enterprises of Yemen - AL-Ghaili, Mohammed; Shah Bali Mahomed, Anuar; Yusof, Raja Nerina Raja (Advances in Social Sciences Research Journal, 2024)
This research investigates the relationships between digitalization, perceived usefulness, attitudes toward using technology, and actual system use of technologies within the context of small and medium-sized enterprises (SMEs) in Yemen. Using a two-step structural equation modelling approach, the research investigates both direct and mediating effects. Data were gathered from 392 SMEs in Yemen by employing a survey research design. The measurement model was estimated to evaluate the constructs' accuracy, while the structural model was analyzed to investigate the proposed relationships. Findings reveal that SME digitalization significantly enhances perceived usefulness, which positively influences users' attitudes toward technology adoption and subsequently drives actual system use. Specifically, the analysis shows that improvements in digitalization practices lead to heightened perceptions of usefulness and favorable attitudes, ultimately resulting in increased actual system use. Moreover, the results indicate that perceived usefulness and attitudes serve as significant mediators between digitalization and system use. This research contributes to understanding how enhancing perceived usefulness and fostering positive attitudes can facilitate technology adoption in SMEs, providing important implications for practitioners, policymakers, and researchers focused on digital transformation. Overall, the findings emphasize the importance of strategic digitalization efforts to improve operational efficiency and promote successful technology acceptance in small and medium enterprises.